THE IMPACT OF ARISAN JULO-JULO ON THE INCOME OF THE LOWER MIDDLE CLASS IN KURANJI, PADANG CITY AND A REVIEW FROM THE PERSPECTIVE OF ISLAMIC ECONOMICS - Eka Putra, Doni; Wahyudi, M.; Khaira, Melati (Universitas Islam Lamongan, 2024)
This study aims to determine the effect of arisan julo-julo on the income of lower-middle class people in Kuranji District, Padang City. The population in the study were poor people in Kuranji District collected through the PKH assistance program as many as 3,378 heads of families. By using the slovin formula, 97 people were obtained as samples. Sampling in this study was carried out by purposive sampling. This type of research is quantitative research that aims to determine the degree of relationship and pattern or form of influence between two or more variables, where with this research a theory will be built that functions to explain, predict and control a phenomenon. The data analysis technique used is descriptive and linear regression with hypothesis testing. The results of the study indicate that the Julo-julo variable has a positive and significant effect on community income.